A new flavanol from the roots of Daphne genkwa. Issue 12 (2nd December 2019) - Wang, Rui; Tong, Ling; Liu, Cai-Yun; Guo, Cong
Abstract: The phytochemical investigation of the roots of Daphne genkwa yielded six secondary metabolites, including a new flavanol derivative, (2R, 3S)-5, 7, 4′-trihydroxy-8-methoxycarbonylflavanol (1 ), and five known compounds (2 –6 ). The molecular structures of the isolated constituents were elucidated on the basis of extensive spectroscopic analysis, including UV, IR, NMR, and MS, and comparison with literature data. Furthermore, the cytotoxic activity of 1 and 2 against A549, HL-60, SMMC-7721, MCF-7, and SW480 cell lines was also described. Graphical Abstract: uf0001